Participation in school councils: from resisance to managerialism toward school justice (Foro de Educacion, 2018)
In the 1980s, Brazil began the process of redemocratization of public institutions, breaking with a period of 20 years of military dictatorship. A new Constitutional Charter was drawn up with the active participation of all Brazilian society organized in social movements. In 1988 the Federal Constitution (CF) established the principle of democratic management of the public education. In 1996 the National Education and Guidelines Law (LDBEN) proposes the participation of the school and local community in deliberative school councils with representation of all the school actors – parents, students, employees, teachers and school leaders. This study discusses the principle of democratic management of public school based on the organization of deliberative School Councils as instances of production of school justice. Based on relevant legislation and literature of the area, the study develops a critical discussion about the role of the board when faced with the new conceptualizations of school management that arise from international organizations for the reform of capitalist education systems. This study also indicates a perspective of school justice that is based on discussions concerning the public school as a space for the construction of social justice. And, finally, the study indicates that, in Brazil, the equal participation of both the school and local communities in School Councils is an ongoing process.